(untitled) (American International Journal of Education and Linguistics Research, 2020)
Alternative assessment has been the focus of many educational researches in EFL classroom. This study was carried out to highlight the definition, characteristics and effects of alternative assessment in EFL context by reviewing current research on assessment. The research consisted of a systematic review of the empirical studies on alternative assessment in EFL classroom. Focusing solely on online search, many studies were found but only (n=24) met the inclusion criteria involving a total of (n=1588) participants. Also, it aimed to scrutinize the methods, participants and findings of the selected studies as well as the locations where they were conducted. The findings indicated that most of the studies (18 out of 24) reported positive effects of employing alternative assessment on language learning skills in EFL classroom. The results also show that the dominant method employed in the articles was quantitative where students were the main focal point involved in the research as their participants. The study is further concluded with a discussion on definition, characteristics and effects of alternative assessment in EFL context.